Sociocultural aspect of the history of the Kazakh woman (Journal of Philosophy Culture and Political Science, 2018)
The problems of the upbringing of the woman’s personality affect the deepest foundations of newthinking. In conditions of transition to market relations, consideration of the role of the Kazakh woman inthe family, in society is necessary, because the recognition of women’s rights in Kazakhstan as an integraland indivisible component of universal human rights is still too formal and not rooted in the public consciousness.This expresses the relevance of this article. The purpose of this article is to consider the historyof the socio-cultural development of a Kazakh woman. The scientific significance of the work lies in thefact that the current state of women in Kazakhstan can not be examined without historical aspects of thesocio-cultural development of women. The practical importance of the work lies in the examination ofdocuments, archival materials, a comparative analysis of the work of scientists-researchers: anthropologists,culturologists, historians, philosophers, sociologists about the place and role of women in the historyof Kazakhstan. The method of secondary research analyzes the work of scientists and their concepts aboutwomen of the East, as well as the author’s own views in the process of analyzing these works. The mainresults are that a theoretical analysis of the status and role of women in the Kazakh society has been carriedout, as well as a modern cultural view of the problem. In the course of work on this problem, the followingconclusions were obtained by the method of secondary research: a method of comparative analysisrevealed the way of life of the eastern woman, special features of character in the life of women of Kazakhs,Uzbeks, Tajiks were singled out. Conclusions are drawn that the living conditions, both in historical retrospect,and the current state of female Kazakhs are heavier than those of Tajiks and Uzbeks. The value ofthe work lies in the fact that a sociocultural perspective on the history of the development of the Kazakhwoman is given. Full and equal participation of women in political, economic, social and cultural life atthe level of the republic should become the main goal of state policy in the field of improving the statusof women in Kazakhstan. And this, above all, affects the formation of a person - a woman.Key words:Personality education of women, the social-political life, the greatness of the woman, the kazakh woman.Key words: Personality education of women, the social-political life, the greatness of the woman,the kazakh woman.